(untitled) (Global Journal of Science Frontier Research, 2024)
This paper proposes mass interaction principle (MIP) as: the particles will be subjected to the random frictionless Brownian motion by the collision of space time particle (STP) ubiquitous in spacetime. The change in the amount of action of the particles during each collision is an integer multiple of the Planck constant h. The motion of particles under the action of STP is a Markov process. Under this principle, we infer that the statistical inertial mass of a particle is a statistical property that characterizes the difficulty of particle diffusion in spacetime. Within the framework of MIP, all the essences of quantum mechanics are derived, which proves that MIP is the origin of quantum mechanics. Due to the random collisions between STP and the matter particles, matter particles are able to behave exactly as required by the supervisor and shepherd for all microscopic behaviors of matter particles. More importantly, we solve a world class puzzle about the anomalous magnetic moment of muon in the latest experiment, and give a self-consistent explanation to the lifetime discrepancy of muon between standard model prediction and experiments at the same time. Last but not least, starting from MIP, we prove the principle of entropy increasing and clarify the physical root of entropy at absolute zero.